Marketplace governance in the context of empowering MSMEs inside the realm of online shopping - Eny Haryati; Amirul Mustofa; Litafira Syahadiyanti; S. Suyanto; Sri Juni Woro Astuti (Universitas Muhammadiyah Malang, 2023)
The development of online markets in Indonesia that sell imported goods at low prices has caused many MSMEs to go collapse. To accelerate the Sustainable Development Goals, especially achieving the goal of